Increased Expression of Endoplasmic Reticulum Stress and Unfolded Protein Response Genes in Peripheral Blood Mononuclear Cells From Patients With Limited Cutaneous Systemic Sclerosis and Pulmonary Arterial Hypertension. Issue 5 (23rd April 2013) - Lenna, Stefania; Farina, Alessandra G.; Martyanov, Viktor; Christmann, Romy B.; Wood, Tammara A.; Farber, Harrison W.; Scorza, Raffaella; Whitfield, Michael L.; Lafyatis, Robert; Trojanowska, Maria
Abstract: Objective: Pulmonary arterial hypertension (PAH), a common complication of limited cutaneous systemic sclerosis (lcSSc), is associated with alterations of markers of inflammation and vascular damage in peripheral blood mononuclear cells (PBMCs). Endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) have been implicated in autoimmune and inflammatory diseases. The goal of this study was to assess whether markers of ER stress and the UPR are present in PBMCs from lcSSc patients with PAH. Methods: PBMCs were purified from 36 healthy controls, 32 lcSSc patients with PAH, and 34 lcSSc patients without PAH. Gene expression in healthy control PBMCs stimulated with thapsigargin was analyzed by DNA microarray. Genes were validated by quantitative real‐time reverse transcription–polymerase chain reaction in PBMCs from healthy controls and lcSSc patients. Results: Several ER stress/UPR genes, including BiP, activating transcription factor 4 (ATF‐4), ATF‐6, and a spliced form of X‐box binding protein 1, were up‐regulated in PBMCs from lcSSc patients, with the highest levels in patients with PAH. Thapsigargin up‐regulated heat‐shock proteins (HSPs) and interferon (IFN)–regulated genes in PBMCs from healthy controls. Selected HSP genes (particularly DnaJB1) and IFN‐related genes were also found at significantly elevated levels in PBMCs from lcSSc patients, while IFN regulatory factor 4 expression was significantly decreased. There was a positive correlation between DnaJB1 and severity of PAH (measured by pulmonary artery pressure) (r = 0.56, P < 0.05) and between ER stress markers and interleukin‐6 levels (r = 0.53, P < 0.0001) in PBMCs from lcSSc patients. Conclusion: This study demonstrates an association between select ER stress/UPR markers and lcSSc with PAH, suggesting that ER stress and the UPR may contribute to the altered function of circulating immune cells in lcSSc.